(untitled) (Revista CIATEC-UPF, 2011)
Numerical solutions for heat transfer problems are usually obtained using an algorithm implemented in a sequential programming language. Despite a powerful set of tools that can be useful in many heat transfer problems, electronic spreadsheets have not been used in these sorts of problems, except for less complex issues. That is partially due to the dificulty in simulate loop iterations in electronic spreadsheets. In the present work a relatively complex phase change transient heat transfer problem is solved by coupling the spreadsheet iteration facility with the time increase required by the problem’s physics. Besides, the energy conservation equation is written based on an enthalpy formulation and the finite volume method is used for the discretization of the corresponding differential equation.